High-power laser diode based on graded AlGaN electron-blocking heterojunction
By adopting a single-layer gradient AlGaN layer structure in a gallium nitride-based laser, the leakage current problem caused by electron leakage to the p-region is solved, and more efficient laser performance and stable low-temperature work are achieved, simplifying the growth process.
Patent Information
- Application Number
- CN202110088818.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-01-22
AI Technical Summary
In the process of increasing the power of gallium nitride-based semiconductor lasers, the problem of sudden drop in efficiency is mainly caused by the increase in leakage current, especially due to the problem of electron leakage into the p-zone. Existing solutions such as the electron barrier layer (EBL) design will be correct. The hole current creates a barrier, reduces the injection efficiency, and is difficult to achieve effective doping and activation in the case of high Al components and thin layers.
Using a single-layer gradient AlGaN layer instead of the traditional electron barrier layer and restriction layer structure, the p-type gradient AlxGa1-xN layer from 0.1 to 0 from the bottom to the top is achieved by combining Mg doping regulation. electron barrier and better hole injection effect.
It significantly reduces leakage current, improves the efficiency of the laser, and maintains a high hole concentration and stable resistance in low temperature environments, simplifies the growth process and avoids the lattice mismatch problem of high Al component layering.
Smart Images

Figure CN114825047B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a semiconductor laser diode, in particular to a gallium nitride-based semiconductor laser diode. Background Art
[0002] Gallium nitride (GaN)-based semiconductor laser diodes (LDs) have the advantages of high efficiency, low threshold, small size, and easy integration. They are widely used in lighting, display, information storage, biochemistry and other fields.
[0003] Currently, GaN-based lasers are developing towards high power, but in the process of increasing power, lasers face the problem of efficiency droop. It is generally believed that one of the important reasons for the decline in laser efficiency is the increase in leakage current, the physical origin of which is the deterioration of hole injection effect and the leakage of high-energy electrons into the p-type region.
[0004] To solve the problem of electron leakage to the p-region, the currently widely used solution is to add a high Al component electron blocking layer EBL (electron-blocking layer) of several to more than ten nanometers in front of the p-type aluminum gallium nitride (AlGaN) confinement layer, thereby forming a GaN / AlGaN heterojunction barrier for electrons. However, this design will bring a series of theoretical and technical difficulties:
[0005] 1. Since the Al component of the EBL layer is significantly higher than that of the p-type confinement layer, a heterojunction is formed between the two layers, which blocks the hole current while blocking electrons, thus reducing the hole injection efficiency;
[0006] 2. Since the EBL layer is very thin, some electrons will cross the barrier layer through the quantum tunneling effect, resulting in leakage. Although increasing the Al component or thickness of the EBL layer can enhance the blocking effect on electrons, it will also increase the difficulty of hole injection and lead to excessively high series resistance;
[0007] 3. The EBL layer generally uses AlGaN with an Al content of 15% or even higher. For common blue light LDs, such a high Al content and the precise thickness of several nanometers make growth difficult;
[0008] 4. The EBL layer requires a high level of p-type doping to facilitate hole injection, but it is very difficult to achieve effective doping and activation at such a high Al composition and extremely small thickness. Summary of the invention
[0009] In order to solve the above difficulties, the present invention provides an electron blocking heterojunction high-power laser diode based on a graded composition AlGaN layer, in which the double-layer structure of the electron blocking layer and the confinement layer is replaced by a single-layer graded AlGaN layer.
[0010] The laser diode provided by the present invention comprises a substrate and an n-type lower limiting layer, a lower waveguide layer, an active region, an upper waveguide layer, a p-type gradient Al x Ga 1-x N layer, p-type GaN contact layer, in which p-type gradient Al x Ga 1-x The Al content of the N layer near the n region is higher, and the Al content near the contact layer gradually changes to 0, that is, the p-type gradient Al x Ga 1-x The Al component content x of the N layer changes linearly from a value of 0.1 to 0.2 from bottom to top.
[0011] In the laser diode epitaxial structure of the present invention, a single layer of p-type graded Al is used on the upper waveguide layer. x Ga 1-x The N layer replaces the "EBL + upper confinement layer" in the traditional structure. x Ga 1-x The Al component content x of the N layer changes linearly from 0.15 to 0 from bottom to top. The Mg doping concentration in the gradient layer is preferably 1E17 / cm 3 ~1E20 / cm 3 .
[0012] The p-type graded Al x Ga 1-x The thickness of the N layer is preferably 300 to 600 nm.
[0013] In the laser diode epitaxial structure of the present invention, the substrate is preferably an n-type GaN self-supporting homogeneous substrate; the n-type lower confinement layer is preferably an n-type AlGaN lower confinement layer; the lower waveguide layer can be an unintentionally doped or n-type GaN lower waveguide layer, or an unintentionally doped or n-type InGaN lower waveguide layer; the active region is preferably an InGaN multiple quantum well; the upper waveguide layer can be an unintentionally doped GaN upper waveguide layer, or an unintentionally doped InGaN upper waveguide layer; the p-type GaN contact layer is preferably a p-type GaN contact layer with high Mg doping, and the Mg doping concentration is generally 1E20 / cm 3 above.
[0014] In the laser diode of the present invention, the graded AlGaN layer simultaneously bears the functions of the light field confinement layer and the electron blocking layer, but has more excellent properties, including:
[0015] 1. The lower end of the graded layer has a higher Al component, and thus has a lower refractive index than the waveguide layer (InGaN or GaN), thereby confining the light field in the waveguide layer to form an optical resonant cavity;
[0016] 2. A GaN / AlGaN heterojunction is formed at the contact point between the lower end of the gradient layer and the upper waveguide layer. Since AlGaN has a larger band gap than GaN, it blocks the electron current from bottom to top at the heterojunction, thereby suppressing the leakage current;
[0017] 3. Since the graded layer replaces the EBL, no heterojunction will be formed between the EBL and the confinement layer to block hole injection;
[0018] 4. By changing the doping concentration of the gradient layer, the relative position of the upper waveguide layer and the gradient layer energy band can be adjusted, thereby increasing the electron barrier, blocking leakage current, and reducing the hole barrier, enhancing hole injection. Usually the heterojunction band order is a relatively fixed quantity, but analogous to the effect of the built-in electric field of the pn junction on the movement of the energy band, the present invention uses doping to regulate the relative potential energy of the waveguide layer and the gradient layer: the current GaN-based laser usually adopts an unintentionally doped upper waveguide layer design, which usually presents a weak n-type (~10 16 cm -3 concentration); when the graded layer is doped with a higher concentration of p-type, its holes will diffuse to the upper waveguide layer, and the migration of carriers destroys the electrical neutrality condition, causing the potential of the graded layer to decrease and the potential of the upper waveguide layer to increase, thereby changing the relative position of the two energy bands;
[0019] 5. The Al component at the top of the gradient layer gradually changes to 0, which is the same as the GaN contact layer component. No heterojunction is formed, which will not block the hole current and is conducive to hole injection;
[0020] 6. The Al component in the upper part of the gradient layer is low, which is conducive to the activation of Mg and ensures a higher hole concentration;
[0021] 7. The graded layer has a polarization doping effect. The Al composition linear graded layer can produce a considerable (~10 18 cm -3 ) holes, and the concentration will not decrease significantly with decreasing temperature, which is conducive to the realization of low-temperature operating GaN-based LD.
[0022] In summary, compared with the traditional laser structure of EBL+limiting layer, since electron tunneling is negatively correlated with the barrier height and barrier thickness, the gradient layer structure of the present invention achieves a higher electron barrier through doping modulation and has a larger barrier thickness. Therefore, it has a better electron blocking effect under high power and the leakage current is significantly reduced; at the same time, since the two heterojunction hole barriers formed at the interface between the limiting layer and the EBL layer and the contact layer are reduced, the gradient layer structure has a better hole injection effect, further reduces the leakage current and improves the efficiency.
[0023] Compared with the single-layer confinement layer structure with a high Al component, the gradient layer structure of the present invention is more conducive to hole injection due to the lower average Al component, and due to the polarization doping effect, the activation of the gradient layer Mg is more stable, the hole concentration is higher, the resistance is smaller, and it is conducive to working in a low temperature environment; in addition, in the epitaxial growth of blue light GaN-based lasers, thick layers with a high Al component are prone to cracking due to lattice mismatch and thermal mismatch, while the gradient layer is relatively easier to grow into a complete crystal. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The conventional structure of using electron blocking layer + limiting layer is different from the p-type gradient Al x Ga 1-x Schematic diagram of the structure of a gallium nitride-based semiconductor laser diode (LD) with a gradient structure of the N layer.
[0025] Figure 2 yes Figure 1 Schematic diagram of the transport principle of laser diodes with traditional structure (left) and gradient structure (right).
[0026] Figure 3 1 and 10 are simulation results of the power-current characteristic curve (a), internal quantum efficiency (b) and leakage current (c) of the laser diodes of the three structures in the embodiment.
[0027] Figure 4 These are the electro-optical conversion efficiency simulation results of the laser diodes with three structures in the embodiment.
[0028] Figure 5 1 and 1 are the energy band simulation results of the EBL structure (a) and the gradient AlGaN layer structure (b) in the embodiment.
[0029] Figure 6 In the embodiment, the gradient AlGaN layer structure has a Mg doping concentration of 1E17 / cm 3 (a), 1E18 / cm 3 (b) and 1E19 / cm 3 (c) The energy band simulation results below.
[0030] Figure 7 1 is the laser output characteristic of the gradient AlGaN layer structure under different Mg doping concentrations in the embodiment.
[0031] Figure 8 Transmission electron microscope photograph of the graded AlGaN layer prepared in the example.
[0032] Fig. 9 1 is the normalized external quantum efficiency-current curve of the LED with the traditional structure and the gradient AlGaN layer structure prepared in the embodiment. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below by way of examples, but the scope of the present invention is not limited in any way.
[0034] like Figure 1 As shown, in the laser diode epitaxial structure involved in this embodiment, an n-type AlGaN lower confinement layer, an n-type GaN lower waveguide layer, an InGaN multiple quantum well, and an unintentionally doped GaN upper waveguide layer are epitaxially grown in sequence on an n-doped GaN self-supporting substrate. After that, for the conventional structure, a p-type AlGaN electron blocking layer and a p-type AlGaN upper confinement layer are successively grown on the upper waveguide layer; while for the gradient structure device of the present invention, a 500nm single-layer linear gradient p-type AlGaN is grown on the upper waveguide layer. x Ga 1-x The N layer replaces the traditional “EBL+upper confinement layer”, in which the p-type graded Al x Ga 1-x The Al component content x of the N layer changes linearly from 0.15 to 0 from bottom to top, and the Mg doping concentration is 1E19 / cm 3 Then, a high Mg-doped p-type GaN contact layer is grown epitaxially, and an anode is plated on it, and a cathode is plated on the substrate side. Finally, the laser diode is prepared through subsequent processes (including photolithography, etching out strip shapes and ridged terraces, cleaving to produce end faces, coating both end faces with reflective films, and scratching out several strip-shaped laser units, etc.).
[0035] (I) In this embodiment, the commercial software Crosslight is used to perform a comparative simulation experiment on three laser diodes having the following structures between the upper waveguide layer and the contact layer:
[0036] Structure 1: EBL (20nm, Al 0.2 Ga 0.8 N, Mg doping concentration 1E19cm -3 )+upper confinement layer (300nm, Al 0.1 Ga 0.9 N, Mg doping concentration 1E19cm -3 );
[0037] Structure 2: Graded AlGaN layer (300nm, Al 0.2→0 Ga 0.8→1 N, Mg doping concentration 1E19cm -3 );
[0038] Structure 3: High Al content confinement layer (300nm, Al 0.2 Ga 0.8 N, Mg doping concentration 1E19cm -3 ).
[0039] The simulation results are as follows Figure 3As shown, among the three structures, Structure 2 using a gradient AlGaN layer exhibits the best power-current curve characteristics and the best internal quantum efficiency characteristics, and among the three structures, under large current (6A) injection, Structure 2 using a gradient AlGaN layer has the smallest leakage current.
[0040] Although the single-layer high Al content confinement layer (structure 3) can also play a good electron blocking effect and has a good internal quantum efficiency, its high Al content leads to a large hole activation energy and a large series resistance, so the electro-optical conversion efficiency is low. The simulation results confirm that among the three structures, the gradient layer structure has a significant advantage in electro-optical conversion efficiency compared with the other two structures (see Figure 4 ).
[0041] The band structure simulation of the EBL structure and the gradient AlGaN layer structure was carried out. The results show that the traditional EBL structure forms a hole barrier at the heterojunction interface between the EBL and the upper confinement layer, which is not conducive to hole injection, while the gradient AlGaN layer does not have this barrier.
[0042] It is worth noting that the optical confinement factors of the active regions of the two structures are 2.13% (EBL structure) and 2.14% (graded layer structure), respectively, that is, the optical confinement effect of the graded AlGaN layer is slightly improved compared with the EBL structure.
[0043] (II) The doping modification test of the gradient AlGaN layer structure was carried out. While maintaining the thickness of 500nm, Al 0.15→0 Ga 0.85 → 1 Based on the N component, Mg doping concentration of 1E17cm -3 , 1E18cm -3 and 1E19cm -3 The results are as follows Figure 6 As shown in the figure, with the increase of doping concentration, the relative position of the energy bands at the contact between the upper waveguide layer and the graded AlGaN layer changes continuously, wherein the conduction band electron potential barrier continues to rise, and the triangular hole potential barrier caused by the polarization effect and carrier migration at the valence band continues to decrease and eventually disappears, which is beneficial to the injection of holes.
[0044] As the doping concentration increases, the efficiency of the laser is significantly improved, and the efficiency drop is significantly improved (see Figure 7 ).
[0045] (III) Based on the design concept of the present invention, Figure 1 Epitaxial wafers with the same structure: 600nm, 3E18 / cm2 and 3E18 / cm3 were grown on a prestressed GaN homogeneous substrate. 3 Concentration of Si-doped Al 0.07 Ga 0.93N lower limiting layer, 300nm, 2E18 / cm 3 The GaN lower waveguide layer is doped with Si concentration, In 0.15 Ga 0.85 N / GaN double quantum well, 300nm unintentionally doped GaN upper waveguide layer. After that, 10nm, 1E19 / cm 3 Concentration of Mg-doped Al 0.15 Ga 0.85 N electron blocking layer and 500nm, 5E18 / cm 3 Concentration of Mg-doped Al 0.07 Ga 0.93 N upper limiting layer; 500nm, 5E18 / cm2 was grown for the gradient structure 3 Concentration of Mg-doped Al x Ga 1-x N gradient layers, where x linearly changes from 0.15 to 0 from bottom to top. Finally, 1E20 / cm 3 The GaN contact layer is doped with magnesium, and the evaporation electrode and etching processes are implemented. Under the continuous current injection of 0-500mA, the luminous power of the traditional structure and the gradient structure device is tested using an integrating sphere, and the normalized external quantum efficiency curve with the injection current is plotted, that is, Fig. 9 By comparing the changes in the normalized external quantum efficiency of the two structures with the current, we can intuitively see the difference in the leakage suppression capabilities of the two structures.
[0046] from Fig. 9 It can be seen that with the increase of injection current, the normalized external quantum efficiency of the gradient AlGaN layer structure is higher than that of the traditional structure. At 500mA, the gradient AlGaN layer is more than twice that of the traditional structure. Since the leakage current ratio can be ignored at 0 injection, and at a smaller current, the decrease in quantum efficiency with the increase of injection current is mainly caused by leakage current, so the normalized external quantum efficiency at a certain current can reflect the degree of leakage. It can be seen that the gradient AlGaN layer has a good inhibitory effect on leakage, especially when the injection current is large. Fig. 9 As can be seen from the figure, after a certain current, as the injection increases, the quantum efficiency of the graded AlGaN structure increases. This may be caused by insufficient Mg doping in the high Al component part of the p-type confinement layer (see Figure 7 ), the injection of unbalanced carriers compensates for this effect when the current increases.
Claims
1. A laser diode, comprising a substrate and an n-type lower confinement layer, a lower waveguide layer, an active region, an upper waveguide layer, a p-type gradient Al x Ga 1-x N layer, p-type GaN contact layer, in which p-type graded Al x Ga 1-x The Al component content x of the N layer changes linearly from a value of 0.1 to 0.2 from bottom to top to 0. x Ga 1-x The thickness of the N layer is 300~600 nm.
2. The laser diode according to claim 1, characterized in that The p-type graded Al x Ga 1-x The Al component content x of the N layer changes linearly from 0.15 to 0 from bottom to top.
3. The laser diode according to claim 1, wherein The p-type graded Al x Ga 1-x The Mg doping concentration in the N layer is 1E17 / cm 3 ~1E20 / cm 3 .
4. The laser diode according to claim 1, wherein The substrate is an n-type GaN self-supporting homogeneous substrate.
5. The laser diode according to claim 1, wherein: The n-type lower confinement layer is an n-type AlGaN lower confinement layer.
6. The laser diode according to claim 1, wherein: The lower waveguide layer is an unintentionally doped or n-type GaN lower waveguide layer, or an unintentionally doped or n-type InGaN lower waveguide layer.
7. The laser diode according to claim 1, wherein: The active region is an InGaN multiple quantum well.
8. The laser diode according to claim 1, wherein: The upper waveguide layer is an unintentionally doped GaN upper waveguide layer, or an unintentionally doped InGaN upper waveguide layer.
9. The laser diode according to claim 1, wherein: The p-type GaN contact layer is a highly Mg-doped p-type GaN contact layer.
Citation Information
Patent Citations
Light-emitting diode with gradient Al component AlGaN conducting layer and preparation method thereof
CN110890447A
GaN-based laser diode epitaxial structure and preparation method thereof
CN111697428A